The Analysis of The Written Test at The End Semester in History Lesson Class X SMA 2 Banda Maluku Tengah Regency - Najirah Amsi (EDUTEC : Journal of Education And Technology, 2019)
The purpose of this study is to determine: (1) the quality of repetition of the semester subjects History class X SMA Negeri 2 Banda viewed from the aspects of materials, construction and language, (2) the distribution of the level of cognitive sphere of Bloom taxonomy measured in repetition of the end of the semester of the eye lesson of class X history of SMA Negeri 2 Banda, (3) quality of repetition of semester subjects of class X history of SMA Negeri 2 Banda viewed from Validity, Reliability, Distinguishing Power, Level of Difficultness, Key Effectiveness and Effectiveness. This research is descriptive quantitative. Data collection techniques are primary data and secondary data. The results showed that these problems have a relatively high (un-reliable) reliability aspect, which is coefficient - 0.1762. From the logical (logical validity) aspect there is one problem that has not been validated yet. From the problem level aspect, 66.67% of the problems are included in the easy criteria, 30% of the questions including medium criteria and 3.33% of the questions including difficult criteria. From the aspect of the differentiating agent, the grains show 7 or 23.33% have bad distinguishing power, 8 grains or 26,67% have weak distinguishing power, 7 grain or about 23,33% have medium distinguishing power, 6 grain or about 20% classified as having both distinguishing power and 2 grains or 6.67% classified as having excellent distinguishing power.